(untitled) (Journal of Geography and Environmental Management, 2016)
The main focus of the paper is on the impact and it’s evaluation of the development of tourism infrastructure on the economic development and regional integration of the border region less attractive from the tourism perspective. The concept of the border region, the methodological suggestions about the analysis of cross-border economy, the theoretical analysis of the impact of physical infrastructure development on attractiveness of a region for tourists are presented in the article. The empirical analysis was done by analyzing the alternatives of setting up the 2nd class camping or 4th class camping in Lithuanian border region, which has borders with Poland. The financial and economic-social analyses of the alternatives are also provided and conclusions are done.